Heart failure enigma in young man: the acute onset of a frequently encountered condition with an unexpected cause. Issue 1 (19th January 2020) - Leonor Lopez, George Luis; Chaparro, Sandra Viviana; Brozzi, Nicholas; Badiye, Amit
Abstract : An 18-year-old male patient presented to the emergency department complaining of new onset chest pain, fever and orthopnoea. Initial workup was remarkable for elevated troponin, diffuse ST-segment elevation on ECG and chest X-ray with enlarged cardiac silhouette. Transthoracic echocardiogram (TTE) demonstrates severe biventricular concentric hypertrophy and pericardial effusion. Also, Coxsackie virus A and B titres were positive, concerning for a classic viral pericarditis. However, despite medical management, the patient became dyspnoeic and hypotensive. Impending cardiac tamponade was observed on repeat TTE, and pericardiocentesis was performed, complicated by pulseless electrical activity cardiac arrest, and ultimately patient requiring venoarterial extracorporeal membrane oxygenation support. Emergent endomyocardial biopsy showed no inflammatory process, and a skin biopsy of a small lesion in the right arm showed unexpected diagnosis of Epstein-Barr virus (+) natural killer/T-cell lymphoma. On initiation of chemotherapy, clinical improvement was observed as evidenced by improving ejection fraction, resolution of pericardial effusion and gradual decrease in myocardial hypertrophy.